2021
DOI: 10.1017/s0033291721002336
|View full text |Cite
|
Sign up to set email alerts
|

Does cognitive improvement translate into functional changes? Exploring the transfer mechanisms of cognitive remediation therapy for euthymic people with bipolar disorder

Abstract: Background Bipolar disorder (BD) is associated with cognitive and functional difficulties, persistent beyond mood episodes. Cognitive remediation (CR) is a psychological therapy targeting cognitive and functioning difficulties. Recent evidence suggests that CR may enhance long-term functioning but transfer mechanisms on functional outcomes have not been explored. We aim to investigate whether and how cognitive gains after CR transfer to functional improvement. Methods We considered data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…For the cognitive variables explored, most overall effects did not vary substantially when removing any of the studies from the synthesis except in two variables: planning and working memory at treatment completion. In the former, the removal of Ott et al (2021b) or Tsapekos et al (2023) rendered the observed effects nonsignificant, and similarly did the removal of either of two studies (Gomes et al, 2019;Lewandowski et al, 2017) in the latter variable. Interestingly, the removal of Douglas et al (2022), which is the only study including patients with different mood states and exploring a combination of psychological treatments, did not change the overall effects.…”
Section: Sensitivity Analysismentioning
confidence: 82%
“…For the cognitive variables explored, most overall effects did not vary substantially when removing any of the studies from the synthesis except in two variables: planning and working memory at treatment completion. In the former, the removal of Ott et al (2021b) or Tsapekos et al (2023) rendered the observed effects nonsignificant, and similarly did the removal of either of two studies (Gomes et al, 2019;Lewandowski et al, 2017) in the latter variable. Interestingly, the removal of Douglas et al (2022), which is the only study including patients with different mood states and exploring a combination of psychological treatments, did not change the overall effects.…”
Section: Sensitivity Analysismentioning
confidence: 82%
“…This suggested that functional difficulties can be reduced through improvements in cognition. 29 Tsapekos et al also found that CR largely improved goal attainment, especially BD with better baseline cognitive performance; severe baseline subjective cognitive, and completed psychological therapies; global cognition; and individual cognitive domains. Their other findings were medium effect size for global cognition, small-to-medium effect sizes for individual cognitive domains, and medium improvement in psychosocial functioning.…”
Section: The Effects Of Cognitive Remediation Therapy In Bipolar Diso...mentioning
confidence: 93%
“…6 A statistically significant effect on the verbal memory was also found after 13 weeks of CR or 10 weeks of ABCR. 28,29 However, the effect was no longer significant at the 6 months follow-up and only the subjective cognitive function persists. 28 CR also could improve psychosocial function by engaging in real-world activities and navigating workplace situations, 14 and medium improvement were shown 31 .…”
Section: The Effects Of Cognitive Remediation Therapy In Bipolar Diso...mentioning
confidence: 97%
See 2 more Smart Citations